EFFORTS MADE BY POLRI AS LAW ENFORCEMENT OFFICIALS IN COMMITTING CRIME WITH VIOLENCE (BEGAL) - Hermawan Sutanto; Syahrul Borman (Transpublika Publisher, 2023)
The crime of robbery involves theft that can lead to the loss of a person's life. To address this issue, the police are empowered with authority and responsibilities outlined in Article 13 of Law Number 2 of 2002. These responsibilities include maintaining security and public order, upholding the law, and providing protection, services, and assistance to the community. This research aims to (1) understand the role of the National Police in combating criminal acts involving violence (such as